STRATEGI PENGEMBANGAN PENGELOLAAN HASIL HUTAN NON KAYU (HHBK) BUAH DURIAN DI ZONA TRADISIONAL, TAMAN NASIONAL MERU BETIRI, KABUPATEN BANYUWANGI - dodit ari guntoro; purwantono purwantono; Nur Kholiq; Alif Aulia Ananda (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
Traditional zone of Meru Betiri National Park (TNMB) has been enacted as a traditional used-area by community who had high dependency on natural resources for generations. Utilization of Non-Timber Forest Products (NTFP) in TNMB in the form of durian was conducted on the area of 25ha spread over 12 blocks with the total number of at least 925 trees (ϕ of >150 cm). Several problems occurred in NTFP management such as: (a) conflict of interest between durian user group and local people, (b) no legacy of NTFP utilization group in TNMB, (3). Low price of durians and no processing durian products. The objectives of this study were to evaluate the internal and external key factors influenced the management of NTFP and to determine the effective strategies to strengthen the sustainable management. Analysis was performed using SWOT with matrix of internal and external factors. The results of this study showed that there were seven (7) factors of each factors of Strength, Weakness, Opportunity and Treat influenced the NTFP management. In general, the conditions of NTFP management in traditional used- area in TNMB was in the position of internally strong and could be improved by developing potential opportunities and reducing the negative effects of potential threads.